The Conference “Urban Memory. The City and Its Inhabitants in the 20th Century”.: 6th–7th November 2008, Brno, Czech Republic. - Bitušíková, Alexandra (Lidé města, 2009)
The team of researchers from the Institute of Ethnology of the Academy of Sciences of the Czech Republic based in Brno together with their colleagues from the Moravian Museum, Archives of the City of Brno and the Institute of History of the Faculty of Arts at the Masaryk University in Brno organized a conference “Urban Memory: The City and Its Inhabitants in the 20th century.” The event took place on the 6th–7th of November 2008 in the heart of Moravia, Brno, in the wonderful Dietrichstein Palace, one of the seats of the Moravian Museum.